Pengaruh Kebijakan Dividen, Kebijakan Hutang, Keputusan Investasi Dan Harga Saham Terhadap Nilai Perusahaan - Enny Arita; Romi Yusmardi (GLOBAL SCIENTS PUBLISHER, 2025)
This study aims to examine the effect of dividend policy, debt policy, investment decisions and stock price on the firm value of mining sector listed on the Indonesian Stock Exchange in 2020-2023. This type of research data is quantitative. The data sources used are secondary data collection method uses documentary data. The population in this study are all mining sector listed on the Indonesia Stock Exchange in 2020-2023 which consist of 88 companies. The sample in this study are 21 mining companies selected based on the criteria (purposive sampling). The data analysis technique used in this study is multiple linear regression testing, hypothesis testing with the help of SPSS software. The results of this research based on the t test show that dividend policy and stock price have a positive and significant effect on the firm value of mining sector listed on the Indonesia Stock Exchange in 2020-2023. Meanwhile, debt policy and investment decisions have no significant effect on the firm value of mining sector listed on the Indonesia Stock Exchange in 2020-2023. Based on the f test, simultaneously dividend policy, debt policy, investment decisions and stock price on the firm value have a positive and significant effect on firm value. Based on the results of this research, independent variables influence the dependent variable by 32%.